2022
DOI: 10.1021/acsami.2c15250
|View full text |Cite
|
Sign up to set email alerts
|

Biological Fixation of Bioactive Bone Cement in Vertebroplasty: The First Clinical Investigation of Borosilicate Glass (BSG) Reinforced PMMA Bone Cement

Abstract: PMMA bone cement has been clinically used for decades in vertebroplasty due to its high mechanical strength and satisfactory injectability. However, the interface between bone and PMMA is fragile and more prone to refracture in situ because PMMA lacks a proper biological response from the host bone with minimal bone integration and dense fibrous tissue formation. Here, we modified PMMA by incoporating borosilicate glass (BSG) with a dual glass network of [BO 3 ] and [SiO 4 ], which spontaneously modulates immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The use of boron-containing BGs has aroused some concerns in biomedical applications, due to a generalized view of boron compounds as toxic chemical entities [ 58 ]. However, there are also numerous studies reporting the low toxicity risk of using boron-containing compounds, including boron-containing BGs [ 59 ]. It is important to understand local toxicity effects of boron-containing BGs and their potential influence on the main organs when these BGs are translated to clinical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of boron-containing BGs has aroused some concerns in biomedical applications, due to a generalized view of boron compounds as toxic chemical entities [ 58 ]. However, there are also numerous studies reporting the low toxicity risk of using boron-containing compounds, including boron-containing BGs [ 59 ]. It is important to understand local toxicity effects of boron-containing BGs and their potential influence on the main organs when these BGs are translated to clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study performed by Zhang et al . [ 59 ] reported that the implantation of borosilicate BG reinforced PMMA bone cement did not elicit acute systemic toxicity or skin irritation and it did not cause visible damage or weight change to the heart, liver, lung and kidney of rats. The biosafety of the composite bone cement was also verified in large animal models, including rabbits and goats and the results of a first human clinical trial were also favorable.…”
Section: Resultsmentioning
confidence: 99%
“…The literature indicated that these problems or risks are because of PMMA's increased elastic modulus, high setting temperature, and lack of bone-bonding ability. 5−8 Currently, the incorporation of inorganic fillers, including hydroxyapatite (HA), 9 β-tricalcium phosphate (β-TCP), 10,11 and bioglass, 12 has proved to be an effective method to reduce the PMMA-associated risks. However, the application of these hybrid bone cements in spinal repair requires more research because of their poor anticollapse properties and injection performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apatite cements were used as dual-setting systems in combination with methacrylated dextran, ammonium polyacrylate, and isocyanate-modified prepolymer . There is also research on the development of new composite bone cements based on PMMA matrix modified with, i.e., CaP, carbon nanotubes, amine-functionalized graphene, or borosilicate glass . Further, Rad et al developed bioactive cement based on three components: PMMA, elastin, and nanohydroxyapatite .…”
Section: Introductionmentioning
confidence: 99%